2018
DOI: 10.1017/s0007114517003506
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of human microarray data shows that dietary intervention withn-3 fatty acids, flavonoids and resveratrol enriches for immune response and disease pathways

Abstract: n-3 Fatty acids, flavonoids and resveratrol are well publicised for their beneficial effects on human health and wellbeing. Identifying common, underlying biological mechanisms targeted by these functional foods would therefore be informative for the public health sector for advising on nutritional health and disease, food and drug product development and consumer interest. The aim of this study was to explore the potential effects of gene expression changes associated with n-3 fatty acids EPA and DHA, flavono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
(62 reference statements)
0
5
1
Order By: Relevance
“…Among other genes, RES increased the expression of those related to the immune response, DC maturation and phagosome formation and was relevant to inflammation and tumorigenesis. A strong upregulation of genes with protumorigenic action was found, in disagreement with evidence commonly reporting the contribution of RES to tumor death through apoptosis induction (Warburton, Vasieva, Quinn, Stewart, & Quinn, 2018).…”
Section: Non-flavonoidscontrasting
confidence: 90%
“…Among other genes, RES increased the expression of those related to the immune response, DC maturation and phagosome formation and was relevant to inflammation and tumorigenesis. A strong upregulation of genes with protumorigenic action was found, in disagreement with evidence commonly reporting the contribution of RES to tumor death through apoptosis induction (Warburton, Vasieva, Quinn, Stewart, & Quinn, 2018).…”
Section: Non-flavonoidscontrasting
confidence: 90%
“…For example ‘normal’ child development could also have an effect on mental health and wellbeing [23 • ,27,33,62]. Similarly a more general approach to maintaining good mental health via diet and exercise could play a role as they could affect the cellular signalling pathways that affect mental health [63,64]. However these issues only illustrate the complexity of defining ‘life style/environment’ and its effect on our wellbeing given the complex nature of life-long experiences in defining our transcriptome, which in turn affects the neurochemistry that ultimately shapes CNS function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some cytokines in the serum were upregulated, such as IL-1α/β, IL-2, and TNF-α. Based on a statistical analysis of human microarray data, a recent study revealed that resveratrol regulated many immune response pathways including peroxisome proliferator-activated receptor α (PPAR-α)/retinoid X receptor α (RXRα) activation, IL-10 signaling, natural killer cell signaling, leucocyte extravasation signaling, and IL-6 signaling [55]. Recently, it was revealed that resveratrol could suppress the aryl hydrocarbon receptor (AhR) pathway, resulting in the reversal of imbalanced Th17/Treg, the main characteristic of immune thrombocytopenic purpura [56].In short, resveratrol could modulate both cellular and humoral immunity to reduce replication and the viability of pathogens, and bidirectionally regulate the related cytokine/chemokine production through the canonical immune response pathways as mentioned above.…”
Section: Immunomodulating Effectsmentioning
confidence: 99%